Determinan Behavioral Intention Pada Platform E- Commerce Di Kalangan Mahasiswa Dengan Integrasi Model Utaut2 Dan Perceived Risk - Pegi Pradana; Farid Wajdi; Imronudin Imronudin (Community Engagement and Emergence Journal (CEEJ), 2026)
The development of financial technology has encouraged the increasing use of buy now pay later (paylater) services on e-commerce platforms, particularly among university students as digital natives. Easy access, payment flexibility, and fast transaction processes have made paylater services increasingly popular. However, the use of these services also creates financial risks, such as consumptive behavior and potential payment defaults. This study aims to analyze the effects of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and perceived risk on the behavioral intention to use paylater services among students in OKU Timur. This research employed a quantitative approach using a survey method through online questionnaire distribution to students who use paylater services. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS software. The results indicate that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit positively affect behavioral intention, while perceived risk has a negative effect. The most dominant variable influencing behavioral intention is performance expectancy. This study concludes that perceived usefulness is the main factor encouraging students to use paylater services, whereas perceived risk tends to reduce their intention to use such services.